Kawasaki Disease With Combined Cholestatic Hepatitis and Mycoplasma pneumoniae Infection: A Case Report and Literature Review - Huang, Shen-Wen; Lin, Sheng-Chieh; Chen, Shih-Yen; Hsieh, Kai-Sheng (Frontiers in Pediatrics, 2022)
Kawasaki disease (KD), also called mucocutaneous lymph node syndrome, is a febrile multisystem vasculitis mainly affecting children younger than 5 years. KD typically manifests as skin lesions and in the lymph nodes and oral and conjunctival mucosa. It may induce coronary artery abnormalities, such as aneurysms, but gastrointestinal and hepatobiliary involvement are not common. We reviewed 32 cases of patients with a diagnosis of KD with hepatobiliary involvement between 2000 and 2021 and present the case of a 4-year-old girl who received a diagnosis of KD with combined cholestatic hepatitis and Mycoplasma pneumoniae infection. In the 33 cases reviewed, in addition to the classical clinical findings of KD, the most common clinical presentations were jaundice and abdominal pain. Moreover, abnormal laboratory results indicating hyperbilirubinemia, cholestasis, and hepatitis, among other conditions, were noted. Abdominal ultrasonography revealed abnormal findings in more than half children with KD with hepatobiliary involvement. Furthermore, cardiac involvement was noted in a high proportion of the patients. In particular, we noted the case of a 4-year-old girl with a rare presentation of 3-day fever combined with abdominal pain and jaundice. Her levels of aspartate aminotransferase, alanine aminotransferase, total bilirubin, direct bilirubin, alkaline phosphatase, and γ-glutamyl transpeptidase were 489 (15–50) U/L, 253 (5–45) U/L, 4.3 (<1.5) mg/dL, 2.4 (<0.2) mg/dL, 337 (134–315) U/L, and 145 (5–32) U/L, respectively. These results were indicative of cholestatic hepatitis. Furthermore, her serological test results for mycoplasma infection were positive. KD was diagnosed because the patient had high fever for more than 5 days and presented with lymphadenopathy on the left side of neck, a polymorphic skin rash, redness of oral mucosa with strawberry tongue, and nonpurulent conjunctival congestion. After intravenous immunoglobulin injection (IVIG) and acetylsalicylic acid administration, the fever subsided rapidly and clinical manifestations, such as jaundice and abdominal pain were mitigated. The laboratory parameters gradually returned to within normal ranges. Echocardiography revealed no aneurysm. In conclusion, KD with cholestatic hepatitis should be considered when pediatric patients present with fever combined with abdominal pain and jaundice. Early treatment with IVIG and aspirin is recommended and can effectively relieve cholestatic hepatitis.